PALM OIL BIODIESEL: CHALLENGES, RISKS AND OPPORTUNITIES FOR REDUCING AND REPLACING THE NON-RENEWABLE FOSSIL FUEL DEPENDANCY - A REVIEW - Erinto Simbolon; Lies Aisyah (Scientific Contributions Oil and Gas, 2013)
Biodiesel is a renewable source of energy which is expected to play a signifi cant role for reducing andreplacing the existing non-renewable fossil fuels. Palm oil is one source of biodiesel feed stock which hasbeen used for many years and gave so many advantages such as high oil yield, cheap to produce and torefi ne, has similar characteristics with petroleum-derived diesel, and has lower emission. However, someissues, such as food stock security, land use changes, and biodiversity extinction, have arisen which needto be considered and solved wisely. Life cycle assessment (LCA) study shows a positive net energy and anet positive sequestration on GHG emission (up to some level of conversion from palm oil to biodiesel)which means biodiesel from palm oil has a high potential to replace fossil fuel and also an environmentalfriendly fuel.